2004
DOI: 10.1007/s10288-004-0044-8
|View full text |Cite
|
Sign up to set email alerts
|

Upper bounds for revenue maximization in a satellite scheduling problem

Abstract: This paper presents upper bounds for the Satellite Revenue Selection and Scheduling problem (SRSS). A compact model of this generalized Prize Collecting Traveling Salesman Problem with Time Windows is defined and enriched with valid inequalities based on task interval reasoning. The non-concavity of the objective function to be maximized is also studied. Finally a Russian Dolls approach combines bounds on nested sub-problems. These first upper bounds for the SRSS problem are compared to best known solutions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Mathematical programming: Benoist et al [5], Habet et al [25], Lemaître et al [28] and Tangpattanakul et al [48] developed general mathematical programming models for EOS scheduling. Liao et al [31], Lin et al [32,33] and Marinelli et al [39] proposed the time-indexed formulation of EOS scheduling, and established integer programming models.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Mathematical programming: Benoist et al [5], Habet et al [25], Lemaître et al [28] and Tangpattanakul et al [48] developed general mathematical programming models for EOS scheduling. Liao et al [31], Lin et al [32,33] and Marinelli et al [39] proposed the time-indexed formulation of EOS scheduling, and established integer programming models.…”
Section: Previous Workmentioning
confidence: 99%
“…Exact algorithms: Bensana et al [6] proposed a depth-first branch and bound algorithm for SPOT-5 satellite scheduling. Also, Benoist et al [5], Bensana et al [6] and Verfaillie et al [52] suggested Russian Doll search algorithms, which are based on branch-andbound but replace one search by n successive searches on nested subproblems, using the results of each search when solving larger subproblems, to improve the lower bound on the global valuation of any partial assignment. Besides, Gabrel et al [20] and Lemaître et al…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Bensana et al [4] structured a depth first branch and bound algorithm on the basis of constraint satisfaction model. Benoist and Rottembourg [13] introduced the Russian dolls approach to verify the upper bounds of the satellite scheduling problem with benchmark testing. Considering the EOS scheduling problem is NP-hard [9], the optimal solution is hardly trackable for large-scale EOS scheduling instances.…”
Section: Introductionmentioning
confidence: 99%
“…The satellite image downlink scheduling problem and its variations have been studied by many authors. Some of these works were focused on case studies for specific satellites or space missions [11,14,20] whereas others are more general purpose in nature [9,10,12,15,16,29,31,32,33]. Literature from machine scheduling [7,25,28,27] and resource-constrained project scheduling [19,26] are also relevant in solving the satellite image downlink scheduling problem (SIDSP).…”
Section: Introductionmentioning
confidence: 99%